SEED PRODUCTION TECHNOLOGY OF PANGASIUS FISH (Pangasius sp.) AT THE MOJOKERTO AQUACULTURE INSTALLATION (IPB) - Arif, Muhammad Choirul; Farikhah, Farikhah (Universitas Mataram, 2025)
This study discusses the implementation of technology and management in the seed production of catfish (Pangasius sp.) at the Mojokerto Aquaculture Installation (IPB). A descriptive method was employed, involving observation, interviews, active participation, and the use of secondary sources. Artificial spawning was conducted using Ovaprim hormone, and larvae were reared under controlled environmental conditions. The results showed a fertilization rate of 87% and a hatching rate of 91%. The first nursery phase yielded 673,036 fry, while the second nursery phase produced 538,560 fry, with respective survival rates of 71.5% and 80%. Key success factors included high-quality broodstock selection, proper feed and water quality management, and the use of effective aeration technology. However, challenges such as limited availability of quality broodstock, water quality fluctuations, and lack of skilled personnel persist. The study concludes that the application of modern hatchery technology can significantly improve catfish seed production and has potential for replication in other regions.